Measurements of air quality in kindergartens and schools in the Republic of Slovenia before the COVID-19 epidemic - Muhič, Simon (Strojniški vestnik, 2022)
This article presents measurements of air quality in school and kindergarten facilities, which were carried out in 311 spaces throughout the Republic of Slovenia, before taking measures to improve energy efficiency of measured buildings. During the measurements, the internal dimensions of the spaces were also measured, as well as data on the energy efficiency of buildings and weather data at the time of the measurements. The measurements focused on indoor carbon dioxide concentration levels and air temperature and relative humidity of indoor air. The performed statistical analysis of measurements shows a large dispersion of measured parameters in buildings, which cannot be statistically significantly related to the analyzed quantities. During the occupancy of the spaces, a statistically significant difference in the concentration of carbon dioxide in the indoor air between the spaces of schools and kindergartens was found. The results of the measurements were also evaluated from the point of view of the COVID-19 pandemic. The average value of measured carbon dioxide value during occupancy of the spaces was compared with the results of a model that predicts an airborne transmission risk. The measured average value of relative humidity in kindergartens shows that relative humidity was 37 %, where is the highest infection risk according to recent studies. The measured average carbon dioxide concentration in classrooms and playrooms significantly exceeds the safe concentration, predicted by the model, to prevent COVID-19 spread at the expected six-hour exposure.
Keywords: carbon dioxide monitoring; COVID-19; indoor air quality; kakovost zraka v prostorih; kindergartens; meritve koncentracije ogljikovega dioksida; naravno prezračevanje; natural ventilation; schools; šole; vrtci